Physico-chemical Studies of Metal Extractants: Hydroxamic Acids - Sharma, Kiran; Harjit, Jeena; Pande, Rama (Asian Journal of Chemistry, 2010)
This paper presents the results of the determination of various physicalparameters of N-arylsubstituted /hydroxamic acids. The parameters investigatedare densities, molar volumes and their partition data betweendifferent organic solvent-aqueous systems. An attempt is made to correlatethese data with theoretical calculations based on regular solution theory,and to investigate solubility parameters of these reagents. These reagentsbehave as organic bases in presence of strong acidic solutions. Thus, theirprotonation has been studied in aqueous hydrochloric acid solutions. Therelevant pKBH+ values have been calculated according to Hammett acidityfunction method (HAFM), Bunnett olsen method (BOM) and excessacidity method (EAM) methods.